Changing Weather Patterns in Maize and Wheat Production against the Backdrop of Improved Access to Weather and Climate Information by Farmers in Uasin Gishu County, Kenya - Murgor, D. K. (Africa Environmental Review Journal, 2021)
With the prevailing changing climate presenting globally, regionally and locally at the farm level in most sub-Saharan countries, availability in real time and the subsequent uptake of climate information by farmers in their crop production planning and production process becomes very critical. This is because attaining improved and sustained high crop yield in a rain fed agricultural system largely depends on accurate timing of rainfall onset and cessation dates during growing and harvesting season. To bring this phenomenon into perspective, a study was conducted among maize and wheat growing farmers in Uasin Gishu County. The objective in this study was to determine the influence of climate and weather information access among maize and wheat farmers in Uasin Gishu County as a mitigating factor in the prevailing changing climate. The study was conducted in Moiben, Kesses and Soy sub counties of Uasin Gishu County selected purposively. The study adopted stratified and random sampling procedure to capture representative sample of farmers. A sample of 399 farmers participated in the study in addition to 12 key informants. A pre-tested semi-structured questionnaire and an interview schedule were the main data collection tools. Chi-square and independent sample t-test were employed in the analysis using SPSS (V.16). Results were considered significant at α=0.05. The findings showed that farmers had incurred maize and wheat crop losses due to lack of adequate rain during growing period as reported by 78.6% of the farmers. Maize and wheat yield loss due to too much rain during growing season, near harvest and harvest period was reported by 66.1% of the farmers. These findings portray a vulnerable group of farmers who have incurred losses in their farming enterprise and therefore need urgent interventional measures that include timely access and usage of advisory alerts or climate information in farming decisions. Similarly, a positive response from 79.4% of farmers reported that after utilization of information on weather and climate from the meteorological department, they were able to successfully apply fertilizers to their crop, weeding and application of agro-chemicals. They were also able to delay commencement of planting to onset of long rains season to avoid losses. Farmers have inculcated coping strategies like crop diversification to mitigate against weather related risks in their farming practice as revealed by 52.7% of the farmers. An average of 58.8% of the farmers reported that they had substituted the growing of both maize and wheat with beans when weather forecast data revealed prevalence of erratic rainfall in the growing season. This however needs to be supported through policy enhancement on crop diversification. Despite the ability to mitigate, farmers often remain vulnerable to climate variability due to the fact that their indigenous knowledge system and experience gained over time over time growing maize and wheat have a greater influence in their farm level decisions. The results further showed that there was a significant relationship between access of climate and weather information and its usage by farmers (Chi = 87.263, P < 0.001). Therefore, the need to repackage climate information to formats that support ready access by farmers is critical if the weather forecasts have to remain relevant to farmers at the farm level and if there has to be ownership and sustainability of any kind. It is clear as explained by farmers that agro-meteorological services should target the use of available tools like mobile phones especially messaging service to disseminate their products and services to the farmers as these tools are widely accessible to farmers.